2005
DOI: 10.1108/14635770510582907
|View full text |Cite
|
Sign up to set email alerts
|

A typology of “best practices” for a benchmarking process

Abstract: International audienceThe paper aims to provide guidelines of companies in identifying their best practices with reference to a French example

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 4 publications
0
59
0
3
Order By: Relevance
“…Benchmarking against best identified practices, if suitably adopted and adapted, can generate a company considerable profit of performance within a very short time (Maire et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Benchmarking against best identified practices, if suitably adopted and adapted, can generate a company considerable profit of performance within a very short time (Maire et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Once best practices have been identified, companies encounter some difficulties regarding the collection of information that will make its transfer possible [30]. Industry requires support both in identifying the most appropriate 'best practice' to meet its particular requirements and in understanding how the appropriate 'best practice' may be transferred.…”
Section: Discussionmentioning
confidence: 99%
“…Kadash and Al Ahomari (2013) found in their study that the practice of performance benchmarking in private firms in Saudi Arabia was better than public organizations and there was no significant difference between companies based on their sizes. Maire et al, (2005) also found that benchmarking was so popular in French companies, 50 percent of 1000 companies used benchmarking regularly and 80 percent of them suggested that benchmarking is an effective tool of change.…”
Section: Benchmarkingmentioning
confidence: 98%